PERHITUNGAN PEMOTONGAN PPh 21 PADA KARYAWAN KOPERASI JASA DIRGAHAYU MAJU SEJAHTERA DI SAMARINDA MENURUT UNDANG-UNDANG NOMOR 36 TAHUN 2008 - Eka Yudhyani, Kristina Ugan LCA Robin Jonathan (EKONOMIA, 2015)
The legal basis for calculation and withholding of Article 21 is the Income Tax Act No. 36 of 2008 and the Regulation of the Minister of Finance No. 162 / PMK.011 / 2012, of the Guidelines calculation and withholding of Article 21.Problem Formulation of this research is "Do the calculations and proposed tax cuts 21 employees Maju Sejahtera Dirgahayu Service Cooperative in Samarinda in accordance with Law No. 36 of 2008 and the Income Tax reporting in the Annual Income Tax Personal 2013 onwards amounted Taxable Income (taxable income) as the Minister of Finance Regulation No. 162 / PMK.011 / 2012."The purpose of this study was to analyze whether Dirgahayu Forward Service Cooperative Welfare has introduced a system of income tax in accordance with the rules applicable legislation, namely Law No. 36 of 2008 and the regulations under the Minister of Finance No. 162 / PMK.011 / 2012 on Guidelines Payment of Income Tax withholding and Reporting Article 21.The hypothesis of this study is "Allegedly the calculation and deduction of Income Tax Article 21 in accordance with the regulations of Law No. 38 of 2008 and reporting in annual tax returns Income Tax Personal Income Tax in 2013 and beyond is for personal exemption (non-taxable income), as in the Minister Finance No. 162 / PMK.011 / 2012. "Conclusion that the calculation and deduction of income tax to 21 Dirgahayu Forward cooperative Welfare Services conducted a school treasurer in accordance with the Income Tax Act No. 36 of 2008 it is thus the hypothesis is accepted.